Investigation of Inertial Cavitation Induced by Modulated Focused Ultrasound Stimuli - George, Benedikt; Savsek, Ula; Fischer, Dagmar; Ermert, Helmut; Rupitsch, Stefan Johann (Current Directions in Biomedical Engineering, 2022)
A passive cavitation detection setup is used to assess and verify the capability of frequency- and amplitude-modulated ultrasound burst signals on the generation of inertial cavitation. The measurements were conducted with a flow-through tissue-mimicking phantom with a canal of dc = 1 mm in diameter simulating a fine blood vessel. By means of a flow velocity of vf = 50 mm/s circulating blood in the cardiovascular system is imitated. Applying signal frequencies from f = 550 − 950 kHz and peak rarefaction pressures in a range from pPRFP ≈ 0.17 − 1.81 MPa, various ultrasound stimuli with alternating signal parameters were investigated in the absence and presence of a talcum-water mixture acting as cavitation nuclei. By evaluating the broadband emissions in the frequency domain and calculating the voltage spectral density Srm, the results can be compared. The findings of the present study demonstrate that each ultrasound stimulus triggers a similar strength of cavitation noise at the same Mechanical Index, representing a certain pressure. Over the whole frequency and Mechanical Index (pressure) range, each ultrasound signal type generates a voltage spectral density from Srm = 0.25 − 2.25 V/√Hz.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Focused ultrasound; Inertial cavitation; Modulated signals